2021
DOI: 10.4274/tao.2021.6193
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Otorhinolaryngological Emergencies in the Elderly

Abstract: Objective: This study was designed to characterize the distribution of otorhinolaryngological emergencies seen in the geriatric population in one year. In this article we present our results and discuss the differences between our results and those reported in the current literature. Methods: The study was carried out in a tertiary care university hospital. All patients aged 65 years or over that were referred by the general emergency department (ED) to the otorhinolary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The aim of our study was to find out the pattern of otorhinolaryngological diseases in which we observed that most common affected organs among the patients presenting complaints was ear which was followed by head and neck, nose and paranasal sinus, larynx, pharynx and oral cavity (8,9). Presbycusis out of all otological disorder was the most common ear disease among geriatric patients (10).…”
Section: Pattern Of Otorhinolaryngolic Diseases In Geriatric Populationmentioning
confidence: 99%
“…The aim of our study was to find out the pattern of otorhinolaryngological diseases in which we observed that most common affected organs among the patients presenting complaints was ear which was followed by head and neck, nose and paranasal sinus, larynx, pharynx and oral cavity (8,9). Presbycusis out of all otological disorder was the most common ear disease among geriatric patients (10).…”
Section: Pattern Of Otorhinolaryngolic Diseases In Geriatric Populationmentioning
confidence: 99%